Antioxidant effects of Geranium nepalense ethanol extract on H2O2-induced cytotoxicity in H9c2, SH-SY5Y, BEAS-2B, and HEK293 - Sim, Mi-Ok; Jang, Ji-Hun; Lee, Hyo-Eun; Jung, Ho-Kyung; Cho, Hyun-Woo (Food science and biotechnology, 2017)
Oxidative damage leads to many diseases. In this study, we evaluated the antioxidant effects of 70% ethanol extract of Geranium nepalense (GNE) on hydrogen peroxide-induced cytotoxicity in cell lines: H9c2, SH-SY5Y, HEK293, and BEAS-2B. We determined the free radical scavenging activity of GNE using 2,2-diphenyl-1-picrylhydrazyl (DPPH), 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS), and superoxide dismutase-like activities, as well as the polyphenol and flavonoid contents of GNE. The results showed that GNE scavenged DPPH and ABTS radicals in a dose-dependent manner. In addition, it contained abundant contents of total polyphenol and flavonoid contents and strongly suppressed cellular reactive oxygen species, thereby protecting H 2 O 2 -induced cytotoxicity in H9c2, SH-SY5Y, HEK293, and BEAS-2B cell lines. The powerful antioxidant activity exhibited by GNE, both in vitro and in cell systems, was attributed to its free radical scavenging activity. Therefore, GNE may be useful in preventing oxidative stress-induced diseases including Alzheimer’s disease, respiratory inflammatory disease, and chronic kidney diseases.